The beliefs and attitudes of teachers and school leaders on gender equality in Vietnamese primary schools: case studies of four schools. Issue 4 (18th May 2020) - Mai, Dung Thi Thuy; Brundrett, Mark
ABSTRACT: The government of Vietnam has shown a commendable commitment to complete equality in society, including in schools yet there is evidence that gendered attitudes still exist, including in primary schools. The main aims of the research reported in this article were to investigate the lived experience of gender equality in primary schools in Vietnam through an examination of the views of teachers and school leaders and to investigate the challenges facing school leaders in implementing government policy. A qualitative research design was employed that consisted of semi-structured interviews with teachers, Deputy Headteachers and Headteachers in four primary schools in Ho Chi Minh City. The findings from the study revealed that gender equality remains a problematic issue in the primary schools where this study took place. In particular, teachers themselves showed gender bias towards the learning ability of boys and girls in different subjects and it was reported that girls who had early puberty struggled with their learning. Moreover, none of respondents expressed a knowledge of government policy on gender equality. Recommendations include suggestions that further training for teachers is required in relation to this important topic during initial teacher training and whilst in-service.